Multipoint Singular Boundary-Value Problem for Systems of Nonlinear Differential Equations. (19th November 2009) - Baštinec, Jaromír; Diblík, Josef; Šmarda, Zdeněk
Abstract : A singular Cauchy-Nicoletti problem for a system of nonlinear ordinary differential equations is considered. With the aid of combination of Ważewski's topological method and Schauder's principle, the theorem concerning the existence of a solution of this problem (having the graph in a prescribed domain) is proved.